The image of east, in the writings of British travelers, during the Victorian period - yousif Husain Al- Ahmad, Husain (Journal of College of Education, 2020)
This paper deals with the writing of the British Travelers that participated in the exploring the countries they visited or which they have dwelled in.  They described their way of life, then their vision affected the European thought and culture. Their views influenced in the presenting  the east to the western readers. The most prominent figures are Burton, Layard, Doughty and other.  The paper treated the motive of those travelers of missionary, one way and love for adventure on the other hand, as well as, looking for romanticism beside  scientific search and the political purpose. All these helped in forming the image of east that dealt with the European culture for along time.